The Effect of Dagusibu (Get, Save, Use and Dispose of Medicine) Education in Increasing The Knowledge of Cadres Empowering Family Welfare (PKK) in Pematang Ibul Village, Rokan Hilir District - Pratiwi, Denia; Annisa, Nurul (Poltekkes Kemenkes Riau, 2024)
Dagsibu (Get, Use, Store and Dispose of Medicines) is an educational program about health to create the Drug Aware Family Movement (GKSO). The aim of this research is to determine the effect of Dagusibu medicine education using leaflet media in increasing the knowledge of cadres Empowering Family Welfare (PKK) in Pematang Ibul Village, Rokan Hilir Regency. This research used a quasi experimental design method by dividing it into 2 groups, namely control and treatment. Sampling used saturated sampling techniques and statistical analysis of the Independent T-Test. Based on the results of research, providing Dagsibu medicine education without using leaflets can increase the knowledge of PKK mothers on post test scores with good knowledge of 42.1%, sufficient 36.8%, and poor 21.1%. Providing Dagusibu medicine education using leaflet media can increase the knowledge of PKK mothers on post test scores with good knowledge of 78.9%, sufficient 15.8%, and poor 5.3%. the results of the T-Independent test obtained a Sig value. 0.026 < 0.05, which means that Dagusibu medicine education using leaflet media can increase knowledge.